ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PT Bank Mega Tbk Periode 2017-2021 - Muhlis Muhlis; Zeze Zakaria Hamzah; Siana Ria; Rakhmi Amaroh; Faradila Ananda Putri (Economicus : Jurnal Ekonomi dan Manajemen, 2024)
This research aims to determine the financial performance of PT Bank Mega, Tbk in the 2017-2021 period. This research uses two methods of financial report analysis, namely vertical analysis and horizontal analysis on the balance sheet and profit and loss report of PT Bank Mega, Tbk. Vertical analysis is analysis carried out on only one financial reporting period. Meanwhile, horizontal analysis is analysis carried out by comparing financial reports for several periods. The research results show that the financial report performance of PT Bank Mega, Tbk is optimal. Total assets owned have increased during the research period, besides that the total current assets owned are greater than the total liabilities. Total income increased during the research period, although in 2018 it decreased but it was not significant. So the current year's profit continues to increase during the research period.